Penerimaan Pelajar Terhadap Aplikasi MOOC TITAS Versi 2.0 di Universiti Awam Malaysia - Adlina Ab. Halim; Ahmad Nasir Mohd Yusoff; Arfah Ab Majid; Normala Othman; Norasyikin Azri; Nasrina M. Samir (USIM Press, 2024)
Vol. 5 No. 1 (2020): Jurnal Sains Insani